Social drivers and tax revenue: The mediation effect of tax compliance. Evidence from an emerging economy - Simon Akumbo Eugene Mbilla (Cogent Economics & Finance, 2023)
This study examined how social drivers such as culture, tax education, attitude, and equity affect tax compliance behaviour among SMEs in Ghana. Quantitative research approach was adopted for this study. The survey research design was employed for this study, and the data collection instrument was a questionnaire. The sample size of this study comprises of 350 SMEs. The hypotheses were tested with the help of Smart-PLS structural equation modelling version_3. The results revealed that social drivers significantly affect tax compliance behaviour. This study contributes to the body of knowledge, adds to practice and policy by demonstrating that tax compliance has taken on a social dimension in Ghana. While the study has become necessary to improve tax compliance among SMEs, the researcher also seeks to contribute globally to the UN'S sustainable development goals (SDG 10), which aim to reduce inequalities.
Keywords: 330; compliance behaviour; culture; revenue; tax education; tax equity